2014
DOI: 10.1186/1471-2474-15-223
|View full text |Cite
|
Sign up to set email alerts
|

Lower hamstring extensibility in men compared to women is explained by differences in stretch tolerance

Abstract: BackgroundThis study examined whether passive hamstring tissue stiffness and/or stretch tolerance explain the relationship between sex and hamstring extensibility.MethodsNinety healthy participants, 45 men and 45 women (mean ± SD; age 24.6 ± 5.9 years, height 1.72 ± 0.09 m, weight 74.6 ± 14.1 kg) volunteered for this study. The instrumented straight leg raise was used to determine hamstring extensibility and allow measurement of stiffness and stretch tolerance (visual analog pain score, VAS).ResultsHamstring e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 34 publications
2
20
0
5
Order By: Relevance
“…Other studies have also shown no sex diŠerence in joint ROM and PT (Gajdosik et al, 2006;Morse, 2011). However, most previous studies have shown that joint ROM in women is greater than that in men (Cipriani et al, 2012;Davis et al, 2008;Marshall and Siegler, 2014;Miyamoto et al, 2018). In addition, the stiŠness of muscles, tendons and MTUs was greater in men (Blackburn et al, 2004;Kubo et al, 2003;Morse, 2011).…”
Section: Discussionmentioning
confidence: 89%
“…Other studies have also shown no sex diŠerence in joint ROM and PT (Gajdosik et al, 2006;Morse, 2011). However, most previous studies have shown that joint ROM in women is greater than that in men (Cipriani et al, 2012;Davis et al, 2008;Marshall and Siegler, 2014;Miyamoto et al, 2018). In addition, the stiŠness of muscles, tendons and MTUs was greater in men (Blackburn et al, 2004;Kubo et al, 2003;Morse, 2011).…”
Section: Discussionmentioning
confidence: 89%
“…Although there are some studies reporting that females may have greater levels of flexibility than males, these findings are attributed to females having greater tolerance to stretching than males. Marshall and Singer [68] evaluated hamstrings extensibility effects on stretch tolerance and passive stiffness between males and females. They did not find any differences between the sexes and passive stiffness.…”
Section: Sex Differencesmentioning
confidence: 99%
“…Darüber hinaus scheint die gesamte Dehndauer wichtiger zu sein als der Dehnungsumfang. Johnson, Mitchell, Meek und Feland (2014) (Marshall & Siegler, 2014;Weppler & Magnusson, 2010). Marschall (1999) verglich die Effekte von zwei unterschiedlichen Dehnintensitäten.…”
Section: Gestaltung Eines Dehntrainingsunclassified